La relación entre el principio de legalidad en derecho penal internacional y la tipificación internacional de los crímenes de lesa humanidad: una perspectiva histórica - Pacheco de Freitas, José Augusto (2019)
This article reviews the processes of consolidation of the principle of legality and of the criminalisation of crimes against humanity in international criminal law from a historical perspective. It starts with the Nuremberg Tribunal of 1945 and then traces the development of these two processes side-by-side: the enshrinement of the principle of legality in a series of universal treaties protecting human rights between the 1960s and the 1980s and the criminalisation of crimes against humanity in the Statutes for the International Criminal Tribunals for the former Yugoslavia and for Rwanda and in the Rome Statute of the International Criminal Court.